Comparative Efficacy and Safety of Advanced Intravitreal Therapeutic Agents for Noninfectious Uveitis: A Systematic Review and Network Meta-Analysis - Weiting Liao; Zhenyu Zhong; Guannan Su; Xiaojie Feng; Peizeng Yang (Frontiers Media S.A., 2022)
Background: To compare the efficacy and safety of advanced intravitreal therapeutic regimens, including a dexamethasone implant at 350 and 700 μg; a fluocinolone acetonide (FA) implant, 0.2 µg/day, 0.59 and 2.1 mg; intravitreal bevacizumab, 1.25 mg; intravitreal ranibizumab, 0.5 mg; intravitreal triamcinolone acetonide (IVTA), 2 and 4 mg; and standard of care (SOC, systemic therapy) for noninfectious uveitis.Methods: We searched the Cochrane Library database, EMBASE, Medline, clinicaltrials.gov until April 2021 with 13 RCTs (1806 participants) identified and conducted a pairwise and Bayesian network meta-analysis with random effects.Results: No specific regimen showed a statistically significant advantage or disadvantage to another treatment regimen with regard to efficacy. However, the FA implant, 0.59 mg was associated with a higher risk of cataract (RR 4.41, 95% CI 1.51-13.13) and raise in intraocular pressure (IOP) (RR 2.53 95% CI 1.14-6.25) compared with SOC at 24 months. IVTA, 4 mg at 6 months was associated with lower risk of IOP rising compared with FA implant, 0.2 µg/day at 36 months (RR 3.43 95% CI 1.12-11.35).Conclusion: No intravitreal therapeutic regimens showed a significant advantage or disadvantage with regard to efficacy. However, SOC was associated with lower risk of side effects compared with FA implants. IVTA, 4 mg, might be the best choice with lowest risk of IOP rising.Systematic Review Registration:clinicaltrials.gov, identifier CRD42020172953